PRODUKTIVITAS PUBLIKASI ILMIAH DOSEN PERPUSTAKAAN DAN SAINS INFORMASI UNIVERSITAS PADJADJARAN: ANALISIS BIBLIOMETRIK - Grahita, Davina; Prijana, Prijana; Kusnandar, Kusnandar (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
Scientific publications are not only a means of disseminating knowledge, but also an indicator to measure quality and key indicators of productivity that can affect university rankings. The method used in this study is a quantitative approach with bibliometric analysis methods. The purpose of this study is to determine the productivity of scientific publications of Library and Information Science Lecturers at Padjadjaran University over the past 10 years. The results of this study show fluctuations in scientific publication productivity with significant productivity in 2018, amounting to 54 scientific publications. The most productive author in publishing scientific publications is Nuning Kurniasih with a total of 70 documents. Meanwhile, the source that contains the most documents from lecturers of the Library and Information Science Study Program is the Journal of Physics: Conference Series (JPCS) which produces the most scientific publications of 35 articles. There are 50 authors and 11 of them are lecturers of the Library and Information Science Study Program at Padjadjaran University which are divided into 2 clusters. With the author who has the most collaborations or collaborations in a research is Nuning Kurniasih.